The Effectiveness of Bright-English for Beginners application in improving students' vocabulary - Tsania, Cyrila Zahra; Syifa, Farah; Gayatri, Resa Diah; khomarudin, Khomarudin (LINGUAMEDIA Journal, 2023)
Lack of vocabulary is the main problem for Indonesian students who learn English. One of the things that makes learning English difficult is the lack of vocabulary. In order that, the technology development in this current era can be used as a way to improve studentsâ€™ vocabulary. There are many software or applications on phones and laptops that provide learning English. The purpose of this research is to analyze whether the â€œBright-English for Beginnersâ€ application be able to increase studentsâ€™ vocabulary or not. This type of research was included in the type of quantitative research with a group without treatment (control group) and a group with treatment (experimental group) which carry out a pre-test and post-test. Before giving the treatment, both groups were given a pre-test. After giving the treatment, which is an experimental group are taught by â€œBright-English for Beginnersâ€ application and control group without it, the researcher gave a post-test. The results of this include 1) There is a relevant improvement for the group with treatment (experimental group) from the pre-test (before treatment) and post-test (after treatment), 2) There is a significant difference between studentsâ€™ vocabulary utilizing â€œBright-English for Beginnersâ€ application and without using it, 3) Vocabulary learning using the â€œBright-English for Beginnersâ€ application has been proven to be more effective than using the usual method.